1973
DOI: 10.1126/science.179.4076.913
|View full text |Cite
|
Sign up to set email alerts
|

Proton Beam Radiography in Tumor Detection

Abstract: Monoenergetic protons are highly sensitive to density variations and are capable of giving radiographs of very high contrast. As an initial step in exploring their diagnostic potential, protons with energies of 160 million electron volts are used in "contact radiography" on tumor-bearing human brain specimens. The proton radiographs are compared with x-radiographs taken under identical specimen conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…Directly behind the metal object, the fluence enhancements and depletions are observed near the edge of the metal object. This well-understood effect is sometimes called the edge enhancement effect (Koehler, 1968; Schneider and Pedroni, 1995; Steward and Koehler, 1973a, b). The lateral deflections are predominated by multiple Coulomb scattering.…”
Section: Dicussionmentioning
confidence: 99%
“…Directly behind the metal object, the fluence enhancements and depletions are observed near the edge of the metal object. This well-understood effect is sometimes called the edge enhancement effect (Koehler, 1968; Schneider and Pedroni, 1995; Steward and Koehler, 1973a, b). The lateral deflections are predominated by multiple Coulomb scattering.…”
Section: Dicussionmentioning
confidence: 99%
“…The concept of the range-edge proton radiography was proposed by Koehler in 1968 [1]. Subsequently, Koehler and others [2][3][4][5] demonstrated that the high-contrast images obtained by proton radiography can provide improved imaging of low contrast lesions in human specimens over conventional x-ray techniques. Hanson described a proton CT method in 1981 [6,7], in which projections necessary for computer tomography (CT) reconstructions were obtained by measuring the proton energy losses.…”
Section: Introductionmentioning
confidence: 97%
“…Proton radiography and tomography as a diagnostic tool was investigated in the early 1970s [1][2][3][4][5] but was more or less abandoned due to the success of X-ray-computed tomography. With the expansion of proton radiation therapy facilities, renewed interest has been placed in the development of a clinical proton radiography or tomography system.…”
Section: Introductionmentioning
confidence: 99%